Otoritas Sahabat dalam Penyebaran Hadis Wilayah Madinah - Maulana , Rizqi Akbar (Journal of Hadith Studies, 2021)
Hadith studies are constantly transforming to support the direction of the study from the practical methodological side, which is in line with the ever-evolving times. However, the study of hadith cannot be separated from the early history of the emergence and development of hadith. In this case, the companions have a major role that cannot be underestimated, especially the companions in the context of Medina. This study is presented to examine more deeply the characteristics of hadith transmission in the context of the Companions in Medina. These two questions raised to serve as the foundation of the study: first, what were the dynamics of transmission in Medina; second, how did the transmission of hadith in Medina influence the study of hadith in other areas? Both questions will be approached through a descriptive-analytical method based on library research. The results of the study show that the contribution of the Companions in the transmission of hadith has provided the foundation for the continuity of hadith studies in other regions and later generations. Meanwhile, the narration at that time had characteristics such as; limited oral narration, critical attitude in narration, socio-cultural influences in narration, and practical-based forms of teaching and narration. These characteristics led to a pragmatic identity of the narrator, triggering a stagnation in the study of hadith, also known as the period of limitation of narration.